(untitled) (Swiss Medical Weekly, 2011)
QUESTIONS UNDER STUDY: Patients suffering from chronic pain have a high prevalence of depression, resulting in a significant impact on overall quality of life. Our aim was to investigate how long term acute non-specific abdominal pain (NSAP) affected overall physical and mental well-being in patients admitted to our emergency department (ED). METHODS: All patients discharged from the ED with NSAP between 06/2007 and 06/2008 were included for follow up. Current health and well-being was evaluated using the SF-36® health questionnaire. Ordinal linear regression models were chosen to separately assess variables influencing SF-36® outcome, with adjustment for age and gender. Results were expressed as differences of means with corresponding 95% confidence intervals and p-values. RESULTS: Of the 200 patients included (57% female, mean age 33 years), 53 (26.5%) still suffered from NSAP after a 12.5-month mean follow up. Patients with persistent NSAP suffered more from chronic pain (26.4%) or known psychiatric illnesses (15.1%) than unaffected patients (p <0.001 and p = 0.028). Mental (MCS) and physical component scores (PCS) were significantly worse in patients suffering from persistent NSAP, even when adjusted for confounding factors including chronic pain syndromes, pre-existing psychiatric illnesses, other concomitant comorbidities and previous abdominal surgery (p <0.001 for both scores). Other risk factors included chronic pain syndromes, pre-existing psychiatric illnesses, other concomitant comorbidities and previous abdominal surgery. CONCLUSIONS: NSAP persistence may be associated with a decreased quality of life. Emphasis should be put on providing early counselling and support, with the aim of minimising the long term detrimental side effects of NSAP.